Improved Dynamic Range in Fiber-Optic Acoustic Sensing Systems With Enhanced Phase Demodulation Structure - Wu, Haojie; Zhu, Zhijuan; Bao, Qidong; Wang, Wenrui; Ye, Lingyun; Song, Kaichen; Sun, Xinglin (IEEE sensors journal, 2025)
Large dynamic range (DR) is one of the primary requirements in fiber-optic acoustic sensing systems, wherein acoustic signals are converted into phase-modulated (PM) signals for detection. In the signal transduction stage, research has been conducted to increase the phase sensitivity. This allows for the conversion of acoustic signals into PM signals with higher phase modulation indices (PMIs), therefore improving the detection of weak acoustic signals. However, higher PMIs induced by strong acoustic signals correspondingly broaden the signal bandwidth. A phase demodulation structure that provides both high-bandwidth capability and low-noise performance is needed to improve both the upper and lower limits of DR. To solve the contradiction between phase demodulation noise and bandwidth, we proposed a novel phase demodulation structure featuring an enhanced phase acquisition method and an enhanced feedback control algorithm. The enhanced phase acquisition method combines high-precision analog-to-digital converter (ADC) sampling data with high-frequency comparator data, enhancing the capability to capture dynamic phase variations. The enhanced feedback control algorithm incorporates a predictive control method using high-order signal models and Kalman filter (KF) iteration to optimize the phase tracking performance. With the proposed demodulation structure, phase variation in the residual signal is reduced and the residual signal bandwidth is compressed before sampling. This combined approach effectively balances noise and bandwidth. The performance of the proposed structure is validated through simulations and experiments, achieving a DR of 170.1 dB at 1 kHz with a phase resolution of 4 × 10^{-{6}} rad/ \sqrt {\text {Hz}} in practical tests. Based on our estimation, the optimal DR is approximately 211.5 dB at 1 kHz.